Challenges and insights in implementing coordinated care between oncology and primary care providers: a Canadian perspective - Tomasone, J.R. (Curr Oncol, 2017)
We report here on the current state of cancer care coordination in Canada and discuss challenges and insights with respect to the implementation of collaborative models of care. We also make recommendations for future research. This work is based on the findings of the Canadian Team to Improve Community-Based Cancer Care Along the Continuum (canimpact) casebook project. The casebook project identified models of collaborative cancer care by systematically documenting and analyzing Canadian initiatives that aim to improve or enhance care coordination between primary care providers and oncology specialists. The casebook profiles 24 initiatives, most of which focus on breast or colorectal cancer and target survivorship or follow-up care. Current key challenges in cancer care coordination are associated with establishing program support, engaging primary care providers in the provision of care, clearly defining provider roles and responsibilities, and establishing effective project or program planning and evaluation. Researchers studying coordinated models of cancer care should focus on designing knowledge translation strategies with updated and refined governance and on establishing appropriate protocols for both implementation and evaluation.